Resistance Arm Training in Patients With COPD: A Randomised Controlled Trial - Janaudis-Ferreira, T.; Hill, Kylie; Goldstein, R.; Robles-Ribeiro, P.; Beauchamp, M.; Dolmage, T.; Wadell, K.; Brooks, D. (American College of Chest Physicians, 2011)
Background: The study aimed to evaluate the effect of upper extremity resistance training for patients with COPD on dyspnea during activity of daily living (ADL), arm function, arm exercise capacity, muscle strength, and health-related quality of life (HRQL). Methods: Patients were randomly assigned to an intervention or control group. The intervention group underwent arm resistance training. The control group performed a sham. Both groups exercised three times a week for 6 weeks. Dyspnea during ADL and HRQL were measured using the Chronic Respiratory Disease Questionnaire (CRDQ). Arm function and exercise capacity were measured using the 6-min pegboard and ring test (6PBRT) and the unsupported upper limb exercise test (UULEX), respectively. Muscle strength for the biceps, triceps, and anterior and middle deltoids was obtained using an isometric dynamometer. Results: Thirty-six patients with COPD (66 ± 9 years) participated in the study. Compared with the control group, the magnitude of change in the intervention group was greater for the 6PBRT (P = .03), UULEX (P = .01), elbow flexion force (P = .01), elbow extension force (P = .02), shoulder flexion force (P = .029), and shoulder abduction force (P = .01). There was no between-group difference in dyspnea during ADL, HRQL, or symptoms during the 6PBRT or UULEX (all P values > .08). Conclusions: Resistance-based arm training improved arm function, arm exercise capacity, and muscle strength in patients with COPD. No improvement in dyspnea during ADL, HRQL, or symptoms was demonstrated.